Effect of season on semen quality parameters in Murrah buffalo - NITHARWAL, K; SINGH, P; BHAKAT, M; CHAURASIA, A; ABDULLAH, M; PRABHA, C (The Indian Journal of Animal Sciences, 2017)
Seasonal influence on frozen semen quality in Murrah buffalo breeding bulls was determined. Frozen semen samples of 6 Murrah buffalo bulls were collected and semen frozen in 4 different seasons, viz. winter (Dec-Feb), spring (mid Feb-Apr), summer (May-Jun) and rainy (Jul-Aug) were assessed. Samples (12) of each bull, in a season, were evaluated for sperm motility, viability and acrosome integrity. Motility and other kinematics of spermatozoa during incubation (37Â°C) at 0, 30, 60, 90 and 120 min of thawing were assessed with computer assisted semen analyzer. Post-thaw sperm total motility and viability differed significantly among the seasons, the highest was in winter. Sperm plasma membrane integrity, acrosome integrity, progressive motility, rapid motility and other CASA evaluated parameters did not differ significantly among the seasons. Higher values of plasma membrane integrity (PMI), progressive motility, rapid motility, average path velocity (VAP), straight line velocity (VSL), curvilinear velocity (VCL), beat cross frequency (BCF), linearity (LIN) and straightness (STR) were obtained in winter season as compared to other seasons. Post-thaw motility at 0 min and 60 min of post-thaw incubation varied significantly between seasons and higher sperm motility was sustained for a longer period in semen cryopreserved in winter followed by rainy season, summer and spring. It can be concluded from this study that buffalo bull semen produced and frozen during winter season resulted in higher sperm motility, viability and postthaw longer survivability in comparison to other seasons.